Effect of 7-hydroxystaurosporine on glioblastoma cell invasion and migration - MENG Qing-hui; ZHOU Li-xin; LUO Jia-lin; CAO Jian-ping; TONG Jian; FAN Sai-jun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of 7-hydroxystaurosporine (UCN-01), a selective protein kinase C (PKC) inhibitor, on cell growth, migration, and invasion in invasive human glioblastoma U-87MG cells. Methods: PKC activity was determined based on the PKC-catalyzed transfer of the 32P-phosphate group from [g-32P]ATP into a PKC-specific peptide substrate. Cell viability was measured by MTT assay. Cell invasion and migration were evaluated by a Boyden chamber assay and scratch wound assay, respectively. Protein expression was analyzed using Western blot assay. The formation of 3-dimensional cellular aggregates was examined by a cell-cell aggregation assay. Results: UCN-01 treatment resulted in concentration- and time-dependent inhibition of U-87MG cell growth at higher doses (> 100 nmol/L), and reduced cell invasion and migration capability at less cytotoxic doses (